Patterns in the prevalence and wealth-based inequality of cervical cancer screening in India - M. R. Muthuramalingam; V. R. Muraleedharan (BMC, 2023)
Abstract Background Cervical cancer is the second leading cause of deaths due to cancer among women in India. This study assesses the prevalence of cervical cancer screening among women in the 30 to 49 years age-group and its relation to demographic, social and economic factors. The equity in the prevalence of screening is studied with respect to the women's household wealth. Methods Data from the fifth National Family Health Survey are analyzed. The adjusted odds ratio is used to assess the prevalence of screening. The Concentration Index (CIX) and the Slope Index of Inequality (SII) are analyzed to assess the inequality. Results The average national prevalence of cervical cancer screening is found to be 1.97% (95% C.I, 1.8-2.1), ranging from 0.2% in West Bengal and Assam to 10.1% in Tamil Nadu. Screening is significantly more prevalent among the following demographics: educated, higher age group, Christian, scheduled caste, Government health insurance coverage, and high household wealth. Significantly lower prevalence is found among Muslim women, women from scheduled tribes, general category castes, non-Government health insurance coverage, high parity, and those who use oral contraceptive pills and tobacco. Marital status, place of residence, age at first sexual activity, and IUD usage are not significant influencers. At the national level, CIX (0.22 (95% C.I, 0.20-0.24)) and SII (0.018 (95% C.I, 0.015-0.020)) indicate significantly higher prevalence of screening among women from the wealthier quintiles. Significantly higher screening prevalence among wealthier quintiles in the North-East (0.1), West (0.21) and Southern (0.05) regions and among the poor quintiles in the Central (-0.05) region. Equiplot analysis shows a "top inequality pattern" in the North, North-East and Eastern regions, with overall low performance where the rich alone manage to avail screening. The Southern region exhibits an overall progress in screening prevalence with the exception of the poorest quintile, which is left behind. Pro-poor inequality exists in the Central region, with significantly higher prevalence of screening among poor. Conclusion The prevalence of cervical cancer screening is very low (2%) in India. Cervical cancer screening is substantially higher among women with education and Government Health insurance coverage. Wealth-based inequality exists in the prevalence of cervical cancer screening and the prevalence is concentrated among the women from wealthier quintiles.